Structured Qur’anic Learning, Religious Habituation, and Teacher Practice: A Case Study of the Taisir Method - Simbolon, Adinda Al Husna Br; Lubis, Dahlia (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Structured Qur’anic instruction in early childhood education can organize basic reading activities alongside recurring religious practices, classroom routines, and teacher discipline. This study examined the implementation of the Taisir Method at TK Ulumul Qur’an, the religious and social habituation observed among selected pupils, and the participating teacher’s reported pedagogical and religious practices within changing educational conditions. A qualitative descriptive case-study design was employed. Formal data collection was conducted in April 2026 through systematically recorded classroom observations, semistructured interviews with the principal and one teacher, naturalistic conversations with two purposively selected pupils, and analysis of learning records and school documents. The researcher’s prior engagement as a teacher at the school for approximately one academic year provided contextual familiarity with recurring instructional routines. The findings showed that the method organized Qur’anic instruction through the sequential stages of ra’a (seeing), sami’a (listening), and qara’a (reading), supported by small-group learning, collective repetition, individual recitation, gradual targets, and written progress monitoring. The selected pupils repeatedly participated in explicitly religious practices, including prayer and respectful greetings, as well as broader classroom routines involving orderly turn-taking and responsibility for learning materials. The participating teacher reported that the method provided a more systematic framework for lesson preparation, pronunciation modeling, individual evaluation, time management, patience, and religious modeling. The study concludes that, within the institution studied, the Taisir Method connected instructional organization, school-based religious and social habituation, and the participating teacher’s pedagogical practice.